2007
DOI: 10.1002/jip.57
|View full text |Cite
|
Sign up to set email alerts
|

Offender and crime characteristics of female serial arsonists in Japan

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Findings from research on spatial characteristics of arsons, which follow from the typological classification proposed by Canter and Fritzon (1998), have demonstrated that instrumental arsonists were likely to travel further from home to commit their crimes on average and were also likely to have a greater distance between their own arson offenses when compared to expressive arsonists (Wachi et al 2007). Furthermore, Kocsis and Irwin (1997) and Curman (2004) have highlighted that serial arsonists are likely to operate relatively close to their residence.…”
Section: Existing Research On Arsonmentioning
confidence: 96%
“…Findings from research on spatial characteristics of arsons, which follow from the typological classification proposed by Canter and Fritzon (1998), have demonstrated that instrumental arsonists were likely to travel further from home to commit their crimes on average and were also likely to have a greater distance between their own arson offenses when compared to expressive arsonists (Wachi et al 2007). Furthermore, Kocsis and Irwin (1997) and Curman (2004) have highlighted that serial arsonists are likely to operate relatively close to their residence.…”
Section: Existing Research On Arsonmentioning
confidence: 96%
“…The literature is conflicted in this regard. Although firesetters have appeared to be low academic achievers (Anwar et al, 2011) and more likely to be in unskilled employment when compared to non-firesetting comparison groups (Bradford, 1982), contradictory findings have shown no differences between firesetters and nonfiresetters on academic attainment (Harmon et al, 1985;Stewart, 1993;Vaughn et al, 2010;Wachi et al, 2007). Female firesetters' previous engagement with mental health services was 13 notably more likely than the two other comparison groups.…”
Section: Group Differences In Socio-demographic Characteristicsmentioning
confidence: 99%
“…As noted previously, several studies have since tested the model by examining the offence actions and background characteristics of arsonists within the established theoretical framework and have found support for Canter and Fritzon's (1998) findings (Hakkanen et al, 2004;Kocsis & Cooksey, 2002;Wachi et al, 2007). However, several differences in the individual offence actions of offenders were noted when the results of those studies were directly compared with the results of Canter and Fritzon's British sample.…”
mentioning
confidence: 93%
“…Since the introduction of Canter and Fritzon's (1998) Faceted Action Systems classification system for arson, 1 many studies have used the model to explain and predict the behaviour of arsonists (Canter, Bennell, Alison, & Reddy, 2003;Fritzon et al, 2001). Scholars have replicated the model with arsonists from around the world, statistically validating Canter and Fritzon's (1998) thematic findings and providing the much-needed empirical support for the application of the action system framework with criminal behaviour (Hakkanen et al, 2004;Kocsis & Cooksey, 2002;Wachi et al, 2007).…”
mentioning
confidence: 99%